Peningkatan Kapasitas Literasi Lansia Dalam Penggunaan Media Digital Pada Forum Silahturahmi Pensiunan - Fera Tri Susilawaty; Jumrana Jumrana; Marsia Sumule; Santi Indra Astuti; Giri Lumakto; Cecep Ibrahim; Rahmawati Rahmawati; Yunita Simatupang (MENARA RIAU, 2023)
Seniors who are digital immigrants, namely those born when digital media did not yet exist, were forced to move into a completely digital world. Habits and culture are certainly very different. In this dilemma, it is not uncommon for elderly citizens to be targets of misuse of digital devices. So, we carried out this activity to be able to provide knowledge related to digital literacy, train the elderly in fact-checking with methods and tools and be able to make the elderly become agents of digital literacy. The method of this activity is training accompanied by an activity facilitator. Delivery of training with lectures, discussions, and use of fact-checking tools. The results of the training show that participants can know about digital security and personal data protection, can identify hoaxes, and can carry out independent fact checks